Rational design, synthesis and in vitro antimicrobial activity of teixobactin analogues - Ng, Vivian (2019)
The recent discovery of teixobactin, a depsipeptide comprising a linear heptapeptide chain that is tethered to a 13-membered macrocyclic ring, has brought great promise of addressing the global issue of antimicrobial resistance. By binding to vital bacterial cell wall precursors known as lipid II and lipid III, it synergistically interferes with the biosynthesis of the peptidoglycan layer and the wall teichoic acid, respectively. Due to its unique modes of action, teixobactin shows potent antibacterial activity against many Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus and Cutibacterium acnes. Significantly, resistance towards this depsipeptide has yet to emerge since its non-protein targets are not readily altered by simple mutations. Thus, the primary aim of this project is to design and synthesise a series of teixobactin analogues, and to systematically determine a structure-antimicrobial activity relationship using clinically relevant bacteria. To obtain structurally unique analogues, several trifluoromethyl-containing and ω-unsaturated amino acids were prepared by utilising a chiral Ni(II)-glycine Schiff’s base. Meanwhile, two different strategies were investigated for the total synthesis of the teixobactin analogues. The initial attempt, which involved the formation of the 13-membered macrocyclic ring through macrolactonisation (intramolecular esterification) was unsuccessful. An alternative strategy involving the macrolactamisation (amide bond formation) between the residues at position-10 and -11 was then undertaken and this approach successfully afforded the desired macrocyclic ring. Hence, the total synthesis of the teixobactin analogues in this project was achieved by using a combination of a Fmoc/tBu solid-phase peptide synthesis strategy and solution-phase macrolactamisation. Systematic modifications of the analogues were performed by substituting the Ile residue at position-11 with various unbranched amino acids, the guanidino residue at position-10 with NG-methylated arginine derivatives and trifluoromethyl-containing amino acids, the Ala residue at position-9 with an α,β-dehydroamino acid and a β-homoalanine residue, and the N-Me-D-Phe residue at position-1 with a D-Trp residue. An analogue with a truncated N-terminal tail was also prepared by removing the residues at position-2 to -4.